Integrated single minute exchange of die (ismed) approach to improve tandem press line operation output in automotive industry - Azizul Qayyum, Basri (2021)
In today's economic world, competitiveness is characterized by great agitation and extreme conflict. This disturbed environment has compelled firms to renew themselves by implementing various approaches such as Agile, Lean, TPM, TQM, and so on, to remain competitive in the market and achieve their goals successfully. This research is focusing on the production performance of the stamping process in Malaysia’s automotive industry. Most of the changeover or setup time reductions are governed or associated with Shingo’s Single Minute Exchange of Die (SMED) method, which suggests the conversion of internal setup operations to external operations. SMED has been initiated by most of the companies but failed to implement it. Thus, what is observed and evidenced in data collected from industry players is that an unacceptably long time is taken in the die/tooling change process, which grossly affects the planned production output. The most significant direct impact of this situation on the industry is the increase in operating costs due to additional time taken to meet the planned production output. Therefore, this research aims to establish a new framework that can improve the efficiency of the die changeover process, which could lower the overall production cost, which could partially transfer the savings to the consumers. The study was conducted in few stages first, data collection correlates with the automotive stamping premise to create a simulation procedure. Second, analyse the current production output using WITNESS simulation. This simulated output data will later be compared to the actual industrial data. Using a systematic die changeover process, a new alternative framework was proposed. The framework combined "Single Minute Exchange of Die (SMED)", lean tools and simulation to become an "Integrated Single Minute Exchange of Die (ISMED)". It shows that the proposed method decreased the changeover processes from the initial 1509.5 seconds to 750.75 seconds, then further decreased to 569.75 seconds, with a net 62.2% time reduction. In the third stage, the selected process is then subjected to analysis using WITNESS simulation. The result shows that the daily production output has increased gradually from 1,100 pieces to 1,500 pieces, then further increased to 2,145 pieces. The output was later further validated through Delphi Method analysis. The new framework proposed in this study has been verified by five experts selected from various backgrounds in the automotive industry. As evidenced by analytical data, it is believed that this new framework will strengthen the total output in the manufacturing process, especially in the manufacturing of automotive stamping parts.